A clinical comparative study of oral and topical ginger on severity and duration of primary dysmenorrhea - P. Shirooye; F. Hashem-Dabaghian; M. Hamzeloo-Moghadam; M. Afrakhteh; S. Bioos; R. Mokaberinejad (Iranian Society of Pharmacognosy, 2017)
Background and objectives: Primary dysmenorrhea has remained a health problem. This study has compared the effect of oral and topical ginger on severity and duration of primary dysmenorrhea.  Methods: A single-blind randomized trial was conducted on 70 female students with moderate and severe primary dysmenorrhea. The participants were stratified randomized between two groups of oral and topical ginger. The oral group received 250 mg capsules of ginger powder and the topical group applied five drops of ginger oil topically every 6 hours from two days before through the first three days of menstruation for three cycles. The severity and duration of pain, and the number of mefenamic acid consumption were assessed in each cycle. Before-after changes were evaluated in each group and were compared between two groups. Results: The reduction of pain severity was 3(±3.2) in the topical compared to 2.6(±3.4) in the oral group (p